TmDOTA-tetraglycinate encapsulated liposomes as pH-sensitive LipoCEST agents. - Ana Christina L Opina; Ketan B Ghaghada; Piyu Zhao; Garry Kiefer; Ananth Annapragada; A Dean Sherry (PLoS ONE)
Lanthanide DOTA-tetraglycinate (LnDOTA-(gly)₄⁻) complexes contain four magnetically equivalent amide protons that exchange with protons of bulk water. The rate of this base catalyzed exchange process has been measured using chemical exchange saturation transfer (CEST) NMR techniques as a function of solution pH for various paramagnetic LnDOTA-(gly)₄⁻ complexes to evaluate the effects of lanthanide ion size on this process. Complexes with Tb(III), Dy(III), Tm(III) and Yb(III) were chosen because these ions induce large hyperfine shifts in all ligand protons, including the exchanging amide protons. The magnitude of the amide proton CEST exchange signal differed for the four paramagnetic complexes in order, Yb>Tm>Tb>Dy. Although the Dy(III) complex showed the largest hyperfine shift as expected, the combination of favorable chemical shift and amide proton CEST linewidth in the Tm(III) complex was deemed most favorable for future in vivo applications where tissue magnetization effects can interfere. TmDOTA-(gly)₄⁻ at various concentrations was encapsulated in the core interior of liposomes to yield lipoCEST particles for molecular imaging. The resulting nanoparticles showed less than 1% leakage of the agent from the interior over a range of temperatures and pH. The pH versus amide proton CEST curves differed for the free versus encapsulated agents over the acidic pH regions, consistent with a lower proton permeability across the liposomal bilayer for the encapsulated agent. Nevertheless, the resulting lipoCEST nanoparticles amplify the CEST sensitivity by a factor of ∼10⁴ compared to the free, un-encapsulated agent. Such pH sensitive nano-probes could prove useful for pH mapping of liposomes targeted to tumors.